2010
DOI: 10.1002/ijc.25142
|View full text |Cite
|
Sign up to set email alerts
|

IGF1, IGFBP1, and IGFBP3 genes and mammographic density: The Multiethnic Cohort

Abstract: Insulin-like growth factor-I (IGF-I) has mitogenic properties and stimulates cell growth. In this analysis, we investigated the relation between common genetic variation in IGF1, IGFBP1, and IGFBP3, and mammographic density among 819 women of Hawaiian, European, and Japanese ancestry from the Multiethnic Cohort Study. Mammographic density was assessed using a quantitative computer-assisted method. Previously identified tag single nucleotide polymorphisms (SNPs) for IGF1 (26 tag SNPs) and IGFBP1/IGFBP3 (22 tag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…In the study by Tamimi et al, rs4619 in IGFBP1/IGFBP3 region was positively associated with increased MD in a mixed population of premenopausal and postmenopausal women [27], however, this association was not observed in another study [30] nor in our study. Results from the Multiethnic Cohort study showed no association between IGFBP1/IGFBP3 rs10228265, rs1496497 and rs3110697 and MD in the overall analysis, but a significant association was found when the analysis was limited to women with Hawaiian and Japanese descent [30]. In that study, the results were based on data from premenopausal and postmenopausal women pooled together.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…In the study by Tamimi et al, rs4619 in IGFBP1/IGFBP3 region was positively associated with increased MD in a mixed population of premenopausal and postmenopausal women [27], however, this association was not observed in another study [30] nor in our study. Results from the Multiethnic Cohort study showed no association between IGFBP1/IGFBP3 rs10228265, rs1496497 and rs3110697 and MD in the overall analysis, but a significant association was found when the analysis was limited to women with Hawaiian and Japanese descent [30]. In that study, the results were based on data from premenopausal and postmenopausal women pooled together.…”
Section: Discussioncontrasting
confidence: 85%
“…Consistent with our findings, the majority of previous studies investigating IGFBP1 and IGFBP3 SNPs reported a lack of significant association between IGFBP1/IGFBP3 SNPs including rs2854746, rs1553009, rs1065780, rs2132570, rs3110697, rs35539615, rs4619, and rs6670 and MD. These studies include a cross-sectional study among 1,121 of premenopausal and postmenopausal women from the Nurses’ Health Study cohort investigating 13 tagging SNPs [27], a study of 819 pre- and postmenopausal women of Hawaiian, European, and Japanese ancestry from the Multiethnic Cohort study investigating 22 tagging SNPs [30], and a study of 1,916 premenopausal women within the Prospect-EPIC cohort investigating 11 tagging SNPs [47]. In the study by Tamimi et al, rs4619 in IGFBP1/IGFBP3 region was positively associated with increased MD in a mixed population of premenopausal and postmenopausal women [27], however, this association was not observed in another study [30] nor in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of candidate gene studies have attempted to identify variants associated with breast density and suggested that IGF1 polymorphisms are associated with the trait [25][26][27]. These breast density associated polymorphisms, however, do not seem to be associated with increased breast cancer risk [28,29]. More recently, a number of groups have examined the association between GWA study-discovered breast cancer loci and breast density, and have failed to detect consistent associations [30][31][32].…”
Section: Anthropomorphic Traitsmentioning
confidence: 99%